The Handbook of Project-Based Management: Leading Strategic Change in Organizations - J. Rodney Turner (USA McGraw-Hill Education, 2014)
The Most Complete, Current Guide to Project-Based ManagementThoroughly revised and reorganized, The Handbook of Project-Based Management, Fourth Edition focuses on the role of the global project manager in today's high-tech, hyperconnected environment of continuous improvement and innovation. Rodney Turner, editor of the International Journal of Project Management, explains how to implement a proven, structured approach to achieving performance improvement through strategic change. This practical resource describes how to align project goals with organizational goals, maintain governance, and manage project performance and process. An all-new case study runs throughout the book, demonstrating real-world applications of the concepts presented.
Keywords: Project management; (BIN3043-N) Project-Based Management; Projects and Organisations (BIN1070-N)